Method validation of crisaborole using reverse phase high performance liquid chromatography (RP-HPLC) and quantitation of crisaborole in nanoemulsion formulation for its application in ex vivo transdermal permeation study / Mohd Hafiz Mohd Jaafar ... [et al.] - Mohd Jaafar, Mohd Hafiz; Affendi, Tommy Julianto Bustami; Hussain, Zahid; Ramli, Nor Amlizan (Faculty of Pharmacy, 2024)
Crisaborole is a boron containing phosphodiesterase 4 (PDE4) inhibitor which in this study was formulated in nanoemulsion form to treat atopic dermatitis. The study aims to develop and validate a selective analytical method for determining crisaborole in nanoemulsion formulations, facilitating its application in ex vivo transdermal permeation studies for the treatment of atopic dermatitis. Crisaborole was eluted using gradient elution method in reverse phase (C18) chromatography. The mobile phases were comprised of phosphate buffer (pH3) and acetonitrile, which increasing acetonitrile volume from 30 to 95 percent within 15 min with constant flow rate of 0.65 ml/min. Column temperature was set at 40 ºC and detection wavelength was at 252 nm. The method produced linear responses (R2=0.99) in concentrations ranges from 1.56-100 µg/ml (n=7). The developed method was sensitive with limit of detection (LOD) and limit of quantitation (LOQ) values of 1.84 µg/ml and 5.58 µg/ml; respectively. Crisaborole was stable in various working conditions which were within the acceptance value provided by guidelines (±15%). In ex vivo studies, the concentration of crisaborole was plotted in cumulative permeated graph and this quantitative method was proven to provide a selective and sensitive measurement for detection of crisaborole.